Saffman–Taylor instability in eccentric cylinders at gaseous cavitation - Anatoliy A. Monakhov; Nikolay Bukharin (Friction)
Abstract A flow of silicon fluid in the gap between eccentric cylinders was studied experimentally. The condition of gaseous cavitation inception during the rotation of internal cylinder was considered. It was shown that at reduction of the gap between cylinders Saffman–Taylor instability appeared on surface of the internal cylinder and then gaseous cavitation was observed. Possibility of one uniform gas formation appearance under this type of instability was demonstrated.